2021
DOI: 10.3390/rs13193792
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Changes of Land Surface Temperature and the Influencing Factors in the Tarim Basin, Northwest China

Abstract: Land surface temperature (LST) is an important parameter that affects the water cycle, environmental changes, and energy balance at global and regional scales. Herein, a time series analysis was conducted to estimate the monthly, seasonal, and interannual variations in LST during 2001–2019 in the Tarim Basin, China. Based on Moderate Resolution Imaging Spectroradiometer (MODIS) LST, air temperature, air pressure, relative humidity, wind speed, precipitation, elevation, and land-cover type data, we analyzed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…During the transformation, the urban microclimate and landscape ecological risks significantly changed, which affected urban development, the ecological environment and the well-being of human life. The previous literature has shown that landscape ecological risk and LST are associated with road distance [25,33], urban expansion [34][35][36][37], climate change and human activities [38][39][40]. However, mitigating effects on both factors have also been identified that are merely related to their own inherent qualities.…”
Section: Discussionmentioning
confidence: 99%
“…During the transformation, the urban microclimate and landscape ecological risks significantly changed, which affected urban development, the ecological environment and the well-being of human life. The previous literature has shown that landscape ecological risk and LST are associated with road distance [25,33], urban expansion [34][35][36][37], climate change and human activities [38][39][40]. However, mitigating effects on both factors have also been identified that are merely related to their own inherent qualities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to global warming, interannual climate variabilities, such as the El-Nino-Southern Oscillation (ENSO), the North Atlantic Oscillation (NAO), the Pacific Decadal Oscillation (PDO) or the Pacific North American Pattern (PNA), are reflected in the LST time series. Abbas et al [6] observed a significant influence of NAO, ENSO and PDO on anomalies of mean LST over the Tarim Basin in Northwest China. Over Alberta, Canada, the PNA had the greatest influence on LST; however, none of the relationships between atmospheric oscillations and LST warming were significant [9].…”
Section: Atmospherementioning
confidence: 99%
“…To analyze the relationship between multiple variables (e.g., LST, ET and albedo), a multiple regression model can be applied [35]. In addition to classic statistical methods, machine learning techniques have also been employed to analyze influencing factors on LST, e.g., the Random Forest model [6].…”
Section: Spatial Lst Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…LST can be obtained via ground measurements or analysis of remote sensing data based on estimates of the Earth's energy balance model. Although terrestrial measurements are more accurate than satellite imagery, point observations and the dispersion of meteorological stations are the main limitations of their research and application on regional and global scales [24]. Because of that, obtaining LST on an extensive terrain or global scale was not possible until satellite thermal sensors were developed, yet it was difficult to obtain spatial, temporal, and spectral high-resolution satellite imagery because of the relationships between these resolutions [25].…”
Section: Introductionmentioning
confidence: 99%